Streaming Standards and Codecs to improve TV service in mobile environments - Guevara-Vega, Alexander; Montesdeoca Erazo, Jorge Luis; Guevara-Vega , Cathy (Data and Metadata, 2025)
Introduction: Streaming technology has become a means of communication with a high rate of application for audio and video transmission such as television services through cell phones. Public and private companies, organizations or individuals of any kind apply streaming, however, the use of standards is limited so the quality of the transmission is affected. Objective: To apply streaming standards and codecs to support audio and video transmission in a mobile environment. Method: The XP methodology was applied as a framework for the development of a mobile streaming application and the completeness of the functional adequacy feature of ISO 25010 was evaluated. Results: The test plan for the application’s operation was optimally executed. The adequate functionality of the application with respect to its completeness was 84.62%, which qualification is very acceptable. Conclusion: The implementation of new codecs facilitated the streaming transmission of the developed application.